2015
DOI: 10.1370/afm.1863
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Mindfulness-Based Interventions in Primary Care: A Meta-Analytic Review

Abstract: PURPOSE Positive effects have been reported after mindfulness-based interventions (MBIs) in diverse clinical and nonclinical populations. Primary care is a key health care setting for addressing common chronic conditions, and an effective MBI designed for this setting could benefit countless people worldwide. Metaanalyses of MBIs have become popular, but little is known about their efficacy in primary care. Our aim was to investigate the application and efficacy of MBIs that address primary care patients. METH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
69
0
12

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(98 citation statements)
references
References 52 publications
8
69
0
12
Order By: Relevance
“…They provide a combination of psycho-educational treatment combined with homework and follow-up sessions. Results of systematic reviews that evaluated stress management strategies (e.g., relaxation, mindfulness, exercise) among physicians reported that they are effective [2,37]. Moreover, group methods are both more cost-effective and more beneficial than individual counselling sessions [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They provide a combination of psycho-educational treatment combined with homework and follow-up sessions. Results of systematic reviews that evaluated stress management strategies (e.g., relaxation, mindfulness, exercise) among physicians reported that they are effective [2,37]. Moreover, group methods are both more cost-effective and more beneficial than individual counselling sessions [4].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, mindfulness techniques have proved to be successful in the treatment of a wide array of physical, psychosomatic, and psychosocial dysfunctions [34,35,36,37], and there is a growing body of research demonstrating the effectiveness of mindfulness and compassion-based meditation practices for reducing the physical and psychological effects of stress among health care workers [38,39]. …”
Section: Introductionmentioning
confidence: 99%
“…In the research literature acceptance-and mindfulness-based interventions (A/MBIs) are considered together in systematic reviews and meta-analyses (e.g., Cavanagh, Strauss, Forder, & Jones, 2014;Veehof, Trompetter, Bohlmeijer, & Schreurs, 2016;Vøllestad, Nielsen, & Nielsen, 2012). As with other forms of complex intervention, A/MBIs are complex psycho-social treatment packages with interrelated components that have a synergizing effect (Demarzo et al, 2015).…”
mentioning
confidence: 99%
“…Over the last decades, meditation practice has spread in Western countries as a safe and efficacious remedy to counteract distress. Evidence on the efficacy of mindfulness‐based interventions (MBIs) for management of psychological health, both in medical and psychiatric patients, as well as in healthy subjects, has been growing. Mindfulness‐based cognitive therapy (MBCT), incorporating cognitive strategies into the theoretical and practical framework of mindfulness‐based stress reduction (MBSR), is recommended as an adjunctive treatment for unipolar depression, since it has been found effective in reducing current episodes of depression and relapse of the disease …”
Section: Focus On Mental Health and Stress Management: Clinical Effecmentioning
confidence: 99%